Robotics in Germany and Japan Philosophical and Technical Perspectives - Funk, Michael (Peter Lang International Academic Publishing Group, 2014)
This book comprehends an intercultural and interdisciplinary framework including current research fields like Roboethics, Hermeneutics of Technologies, Technology Assessment, Robotics in Japanese Popular Culture and Music Robots. Contributions on cultural interrelations, technical visions and essays are rounding out the content of this book.